Relationship between new technologies and burnout: A systematic literature review - Pinto, Ana (2024)
The rise of digitization in workplaces is transforming how work is managed, presenting both advantages and challenges for safety and health. While new technologies can create safer work environments, they can also contribute to high performance pressure, which negatively affects workers' mental health. This has led to the emergence of psychosocial risks, such as Burnout Syndrome. This study aimed to investigate the link between the introduction of new technologies in workplaces and the development of Burnout Syndrome. A systematic literature review was conducted using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology, focusing on the Web of Science database. The reviewed studies revealed that the scientific community is increasingly discussing this topic, with 66% of the studies being conducted in the last four years. The health sector was the most extensively researched area in this field. The findings suggest that the increase in Burnout Syndrome is associated with insufficient information and training for workers, as well as their insecurity in using advanced technologies.